Alpha-lipoic acid: A promising pharmacotherapy seen through the lens of kidney diseases - George J. Dugbartey; Karl K. Alornyo; Christabel O. Dapaa-Addo; Emmanuel Botchway; Emmanuel K. Kwashie; Yvonne Harley (Current Research in Pharmacology and Drug Discovery)
Kidney diseases have rapidly increased in prevalence over the past few decades, and have now become a major global public health concern. This has put economic burden on the public healthcare system and causing significant morbidity and mortality worldwide. Unfortunately, drugs currently in use for the management of kidney diseases have long-term major adverse effects that negatively impact the quality of life of these patients, hence making these drugs a “necessary evil”. In recent times, antioxidant therapy has been explored as a potential pharmacological avenue for treatment of kidney diseases, and could offer a better therapeutic option with less adverse effect profile. One of such antioxidants is alpha-lipoic acid (ALA), a sulphur-containing multifunctional antioxidant that is endogenously produced by lipoic acid synthase in the mitochondria of many tissues, including the kidney. Burgeoning evidence indicates that ALA is showing clinical promise in the treatment and pharmacological management of many kidney diseases through its antioxidant and other therapeutic properties by activating several protective mechanisms while inhibiting deleterious signaling pathways. In this review, we present ALA as a potent naturally occurring antioxidant, its mitochondrial biosynthesis and pharmacological properties. In addition, we also discuss within the limit of present literature, ALA and its underlying molecular mechanisms implicated in experimental and clinical treatment of various kidney conditions, and thus, may offer nephrologists an additional and/or alternative avenue in the pharmacological management and treatment of kidney diseases while giving hope to these patients.